Challenges in Communicating across Cultures - Adhikari, Kumar (Literary Studies, 2015)
How often do we encounter situations in which we send one message and our listener receives another? Quite a lot, I guess. It is because pragmatic norms and cultural conventions transfer in cross cultural communication. Transfer of speech act strategies and cultural norms from one culture to another is quite normal when people communicate in second language or in cross-cultural communicative context. This is because people often tend to frame their speech acts according to pragmatic norms of their own language and culture. That is why, understanding of cultural norms and values of other cultures, speech acts of different speech/linguistic communities is vitally important in cross-cultural communication for better understanding between people from different linguistic and cultural backgrounds. Otherwise, utterances of people of certain speech community are likely to be misunderstood or misinterpreted by the addressee resulting pragmatic errors. This paper traces some of the complications of communication in cross-cultural communicative context, and also suggests a number of possible ways to deal with them.